The impact of video nutrition education on nutrition knowledge, food selection, and ultra-processed food consumption in adolescents - Alfia Rusfianti; Vitri Widyaningsih; Nur Hafidha Hikmayani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
The processed food and beverage industry in Indonesia is increasing rapidly, one of which is the ultra-processed food (UPF) industry. Adolescents had a high prevalence of UPF consumption habits (67.6 %). Adolescents generally prefer foods that are easy to obtain and have a good taste, such as ultra-processed foods and beverages. Consumption of snacks by adolescents with more than three servings per day at school can cause overweight. Good nutrition education needs to be provided in an effort to increase adolescent knowledge, and it is hoped that there will be changes in nutritional behavior in the selection and consumption of better food. The purpose of this study was to analyze the influence of nutritional education videos on nutritional knowledge, food selection, and the frequency of ultra-processed food consumption. The design in this study uses the Quasi-Experimental research type, using a design (pretest-posttest control group design). The research was conducted at Senior High School (SHS) A and SHS B in Depok City, West Java. The sample in this study comprised 174 adolescents from January to February 2024. Data on nutritional knowledge, food selection, and frequency of UPF consumption were collected before and after the intervention using nutritional knowledge questionnaires, food selection, and FFQ forms. Data analysis was performed using Wilcoxon and different-in-different tests. The results of the Wilcoxon test in the intervention group showed an effect of providing education before and after the intervention nutrition education video on nutrition knowledge on nutritional knowledge (p=0,000) and food selection (p=0,009). In conclusion, video media have an effect on changes in nutritional knowledge. Video media had no effect on food selection or the frequency of UPF consumption.